The Widespread Influence of Great Lakes Microseisms Across the Midwestern United States Revealed by the 2014 Polar Vortex. Issue 8 (20th April 2018) - Anthony, R. E.; Ringler, A. T.; Wilson, D. C.
Abstract: During the winter of 2014, a weak polar vortex brought record cold temperatures to the north‐central ("Midwest") United States, and the Great Lakes reached the highest extent of ice coverage (92.5%) since 1979. This event shut down the generation of seismic signals caused by wind‐driven wave action within the lakes (termed "lake microseisms"), giving an unprecedented opportunity to isolate and characterize these novel signals through comparison with nonfrozen time periods. Using seismic records at 72 broadband stations, we observe Great Lakes microseism signals at distances >300 km from the lakes. In contrast to conventional oceanic microseisms, there is no clear relationship between the frequency content of the seismic signals (observed from ~0.5–5‐s period) and the dominant swell period or resonance periods of the lakes based on their bathymetric profiles. Thus, the exact generation mechanism is not readily explained by conventional microseism theory and warrants further investigation. Plain Language Summary: Besides earthquakes, a large range of signals are recorded by seismic instruments, including cultural activity, wind, and ocean waves. Although these signals are often a hindrance to earthquake studies, they have recently been used as a tool for seismic imaging as well as for studying near‐surface processes. Here we explore the characteristics and spatial area impacted by novel signals arising from wind‐driven wave activity within the Great Lakes of North America. As these signals often blend in to other noise sources (such as ocean waves) they have been difficult to understand and fully characterize. We overcome this difficulty by utilizing seismic records from 2014, when a meandering jet stream led to anomalously high concentrations of ice coverage (92.5% coverage) over the Great Lakes during the early spring. As a consequence of this event, seismic signals generated by the lakes vanished. By comparing seismic records during this time period to previous and subsequent nonfrozen years, we are able to isolate the contribution of lake microseisms and show that they significantly impact seismic recordings across the Midwestern United States. Key Points: Anomalously high ice extent on the North American Great Lakes during the winter of 2014 shut down the generation of lake microseisms Seismic signals from the Great Lakes occur between 0.5 and 5‐s period and are observable at distances >300 km from lake shorelines The Michigan Upper Peninsula observes the strongest signals; these peak at ~1.5‐s period regardless of the swell period in Lake Superior